Non-operative breast pathology: apocrine lesions. Issue 12 (27th November 2007) - Wells, C A; El-Ayat, G A
Abstract : Apocrine metaplasia is a very common finding in the female breast after the age of 25. It is so common that many people regard it as a normal component of the breast. This, however, is only really the case in apocrine sweat glands of the axilla and in the peri-areolar apocrine glands. The apocrine cell does, however, contribute to a number of different breast lesions, some of which are very taxing diagnostically; apocrine variants of both in-situ and invasive cancer are encountered. This review considers the common apocrine metaplastic lesions seen in fibrocystic change as well as apocrine adenoma, apocrine change within sclerosing adenosis, atypical apocrine lesions and apocrine malignancies.